The Complete Letters of Henry James - Zacharias, Greg W. (Litteraria Copernicana, 2017)
The paper presents an insider’s view on the conception, organization and execution of the enormous undertaking of editing The Complete Letters of Henry James. Listing some of the problems the project has encountered, the author honors the people and institutions behind it, and names some of the most surprising and illuminating discoveries it has yielded this far.